AB0836 Coping behaviors for activities of daily living in women who have hands affected due to systemic sclerosis. (23rd January 2014) - Cinar, F.I.; Unver, V.; Cinar, M.; Yilmaz, S.; Simsek, I.; Tosun, N.; Erdem, H.; Yilmaz, F.; Pay, S.; Dinc, A.
Abstract : Background: Patients with systemic sclerosis (SSc) are affected physically and psychologically because of their disease. Hand involvement is seen in many patients with SSc. Hand dysfunction in SSc patients may be caused by Raynaud phenomenon (RP) with finger ulcers, arthralgia, arthritis, tendonitis, weakness and skin thickening, which cause loss of dexterity. SSc patients may present with hand dysfunction that cause difficulties in performing daily activities. Objectives: To determine the challenges experienced by SSc women, whose hands affected, while performing activities of daily living and their coping strategies. Methods: Seventeen patients with SSc whose hands affected were enrolled to this descriptive and cross-sectional study between April 2010 and December 2011. In addition to sclerodactyly, patients who had active digital ulcers, digital ulcer complications (pitting scars, digital amputation, digital necrosis), or digital contractures were all considered hand involvement. Skin thickness was assessed by means of the modified Rodnan skin score. The data were collected by using both a demographic data form and an evaluation of daily activity questionnaire (EDAQ). EDAQ consists of 102 daily activities in 11 dimensions, each containing 4–13 activities and questionnaire for coping strategies. Descriptive statistics are shown in numbers (n) and percentages (%) for the variables obtained by counting and in mean ± standard deviation for variables obtained by measurement. Results: Mean age of 17 women was 49.71±11.74 (32-70) years. Duration of illness was 12.65±8.76 (1-31) years. Sixteen were married. Twelve did not have a paid job. One of them was retired. Seven had diffuse, 12 had limited scleroderma. Rodnan skin score mean value was 11.88±4.77. According to EDAQ the most scored dimensions that patients can do with no difficulty was "toileting", some/much difficulty was "eating" and the dimension that patients unable to do "washing/clothes care". In "eating" dimension the most difficult activities were "opening glass jar, opening juice bottle, opening bottle" requiring the movement of rotation. Their coping strategies for these activities were try to open with a towel, try to remove the edge of the palm with a knife, use the hand palm, help from someone else (spouse, neighbor, etc.). In "washing/clothes care" dimension the most difficult activities were "turning up hem of a skirt, washing up in bowl, cutting out material". They use some coping strategies such as getting help from tailor, washing in the machine instead of hand washing. Conclusions: Impaired hand function is related to activities of daily living difficulties. Therefore, many patients establish a variety of coping methods in order to do daily activities. Determining the appropriate methods of coping with and informing patients about this issue seems important in the rehabilitation of patients. Also, it is important to increase awareness of health professionals who provide counseling. In summary, the coping strategies used by patients can be helpful for the other SSc patients. Disclosure of Interest: None Declared